The Body as a Means of Cultural Awareness and Social Intervention: The Case of Raymond Duncan and Penelope Sikelianos - Katerina (Ekaterini) Diakoumopoulou (Tête-à-Tête, DOI: https://doi.org/10.5281/zenodo.6767564, 2022)
Using the example of the Raymond Duncan family this article will explore the human body as an object of self-determination, a means of overcoming social boundaries, a field of racist shooting and phobic enforcement, a reference point of public outrage and the complex between sociality and corporality, but also as a tool of political vigilance and social intervention. Does a body dressed in a tunic resist the western way of life? Or is it a stereotypical outpouring of people unable to modernize? Is the body instrumentalized as a means of narrating exoticism? The bodies of the Duncan family members are an occasion for discussion in the public sphere, even today.